2023
DOI: 10.1186/s12889-023-17361-5
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological features of SARS-CoV-2 Omicron infection under new control strategy: a cross-sectional study of the outbreak since December 2022 in Sichuan, China

Runyou Liu,
Yang Zhang,
Jingxuan Ma
et al.

Abstract: Background A major shift in the “dynamic zero-COVID” policy was announced by China’s National Health Commission on December 7, 2022, and the subsequent immediate large-scale outbreak of SARS-CoV-2 infections in the entire country has caused worldwide concern. This observational cross-sectional study aimed to describe the epidemiological characteristics of this outbreak in Sichuan, China. Methods All data were self-reported online by volunteers. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…Our study revealed a cumulative incidence of SARS-CoV-2 Omicron infection of 86.4% (95% CI 85.2%-87.7%) among hospital staff from Chengdu Women's and Children's Hospital. As expected, it was higher than that reported among the general population of 74.3% in the same province [12], suggesting a greater infection risk faced by hospital staff during an Omicron outbreak. In addition, our rate was much higher than that previously reported for healthcare workers in other studies, most of which had an even longer time frame than our research [13][14][15][16][17].…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Our study revealed a cumulative incidence of SARS-CoV-2 Omicron infection of 86.4% (95% CI 85.2%-87.7%) among hospital staff from Chengdu Women's and Children's Hospital. As expected, it was higher than that reported among the general population of 74.3% in the same province [12], suggesting a greater infection risk faced by hospital staff during an Omicron outbreak. In addition, our rate was much higher than that previously reported for healthcare workers in other studies, most of which had an even longer time frame than our research [13][14][15][16][17].…”
Section: Discussionsupporting
confidence: 66%
“…BMI: body mass index, SD: standard deviation.a Chi-square test or ANOVA for differences among the three groups: con rmed COVID-19 diagnosis, probable COVID-19, and no COVID-19-like symptoms.Table 2 compares the COVID-19-related characteristics between individuals with a COVID-19 diagnosis and highly suspected COVID-19 patients. The former group reported a greater median number of COVID-19 symptoms(14,) and a higher percentage of individuals taking leave from work due to illness (44.5%) than did participants in the latter group (13, IQR[9][10][11][12][13][14][15][16][17]; 30%). However, no statistically signi cant differences in disease severity (using either admission to hospital or diagnosis of pneumonia as a proxy) were detected between the two groups (p > 0.05).…”
mentioning
confidence: 99%
“…Our study revealed a cumulative incidence of SARS-CoV-2 Omicron infection among hospital staff from Chengdu Women’s and Children’s Hospital to be 86.4% (95% CI 85.2%-87.7%), which was higher than the reported rate of 74.3% among the general population in the same province [ 18 ]. However, since our study was conducted more than one week later, it is uncertain whether hospital staff faced a greater infection risk compared to individuals in the community or if the timing difference influenced the documentation of cumulative incidence rates during a rapid and widespread Omicron outbreak.…”
Section: Discussionmentioning
confidence: 71%
“…Table 2 compares the COVID-19-related characteristics between individuals with a COVID-19 diagnosis and highly suspected COVID-19 patients. The former group reported a greater median number of COVID-19 symptoms (14, IQR [ 11 18 ]) and a higher percentage of individuals taking leave from work due to illness (44.5%) than did participants in the latter group (13, IQR [ 9 – 17 ]; 30%). However, no statistically significant differences in disease severity (using either admission to hospital or diagnosis of pneumonia as a proxy) were detected between the two groups ( p > 0.05).…”
Section: Resultsmentioning
confidence: 99%